The main directions of small business support by the state - Garacayeva Lala Ramiz; Yusibova Sabrin Azer; Hasanova Aygun Aydin; Allahverdiyev Aladdin Vusal (Academics and Science Reviews Materials, 2023)
: The financial capabilities of small and medium-sized enterprises, the structure of financing sources, have an important impact on their economic and investment activity. At present, a system of public and private international financial assistance to small and medium entrepreneurs is operating in Azerbaijan. During the years of independence, certain positive experience was collected in the field of financial assistance to small and medium-sized enterprises. However, despite all this, small and medium-sized entrepreneurs, who play an important role in the country's economy due to their potential, have limited use of financial resources. This limitation also manifests itself in obtaining long and short-term loans. One of the important tasks that need to be solved in Azerbaijan is the activation of the investment activity of small and medium entrepreneurs and the expansion of opportunities to attract financial resources to this section.